A study of resilience among young adult children of alcoholics in Southern India. Issue 3 (2nd April 2020) - Hebbani, Sudharshan; Ruben, Johnson Pradeep; Selvam, Sumithra; Krishnamachari, Srinivasan
Abstract: Young Adult Children of Alcoholics (YACOA) are vulnerable to emotional psychopathology. However, some of them remain healthy and lead a productive life despite growing up in adverse circumstances. The present study aims at understanding the relationship between resilience and positive psychological factors among those healthy YACOA. Participants who were identified as YACOA were enrolled from both urban and rural colleges in Karnataka (India). Among them, those who did not report emotional psychopathology were assessed on measures of Resilience, socio-cultural factors (family support, community support, and participation in religious rituals), Self-efficacy and psychological well-being. They were divided into high and low resilience groups based on the median scores. YACOA with high resilience had a significant positive association with cultural factors of resilience whereas YACOA with low resilience had significant positive association with self-efficacy and sub-categories of psychological wellbeing. Binary Logistic Regression analysis found that socio-cultural factors were found to be associated with high resilience among YACOA. This study has recognized the significance of socio-cultural factors and self-acceptance in enhancing resilience among healthy YACOA. These findings offer insights into the interventions for the wellbeing of the YACOA.